OP0201 Safety, Tolerability, and Functional Activity of MGD010, A Dart® Molecule Targeting CD32B and CD79B, Following A Single Dose Administration in Healthy Volunteers. (15th July 2016) - Pandya, N.; Chen, W.; Lohr, J.; Yao, X.-T.; Burns, R.; Li, H.; Li, H.; Muth, J.; Goldwater, R.; Bonvini, E.; Johnson, S.; Moore, P.; et al.
Abstract : Background: MGD010, a bi-specific Dual-Affinity Re-Targeting, or DART®, molecule, inhibits activated B-cells by delivering a negative signal via simultaneous co-ligation of the inhibitory checkpoint molecule, CD32B (FcγRIIb), with the BCR component, CD79B. This novel-therapeutic approach leverages a physiologic B-cell inhibitory loop leading to signal suppression without B-cell depletion, while targeting all activated B cells rather than subsets, such as those dependent on BLyS for survival. MGD010 is being developed for the treatment of autoimmune disorders. Objectives: A single ascending dose study among healthy volunteers was conducted to assess the safety, tolerability, pharmacokinetics, and functionality of MGD010. Methods: This was a first-in-human, double-blind, placebo-controlled study in which 48 evaluable healthy volunteers were intravenously (IV) administered a single dose of MGD010. Eight (8) subjects were randomized [6:2 MGD010:Placebo] in each of the six (6) dose levels [0.01, 0.1, 0.3, 1.0, 3.0, and 10.0 mg/kg] and followed for safety evaluation. B-cell binding and functional assessment, as measured by ex-vivo calcium (Ca 2+ ) flux, was determined by flow cytometry in peripheral blood samples. Quantitation of immune cell populations, phenotyping of B-cell subsets, immunoglobulin levels and cytokines were also serially evaluated. Results: MGD010 was well tolerated at all dose levels. All related adverse events (AEs) were ≤ Grade 2 and no serious AEs (SAEs) were reported. No subjects had premature discontinuations or infusion reactions, systemic hypersensitivity reactions or injection site reactions. No clinically relevant changes in laboratory parameters, vital signs, or ECG parameters occurred. No substantial decrease in peripheral B-cell counts was observed at any dose level. MGD010 demonstrated linear pharmacokinetic and dose-dependent binding to circulating B lymphocytes. Consistent with its anticipated mechanism of action, administration of MGD010 was associated with a reduction in ex vivo BCR-induced Ca 2+ mobilization in B lymphocytes. Furthermore, a selective dose-dependent, prolonged downregulation of surface IgG BCR expression among circulating CD27 + memory B cells was also observed, supporting a preferential effect on activated memory B cells. Conclusions: These data demonstrate that MGD010 has an acceptable safety profile following a single-dose IV administration of up to the maximal tested dose level and showed pharmacodynamic activity consistent with its design. The results support continued development of MGD010 in patients with autoimmune disorders. Disclosure of Interest: N. Pandya Shareholder of: MacroGenics, Employee of: MacroGenics, W. Chen Employee of: MacroGenics, J. Lohr Employee of: MacroGenics, X.-T. Yao Employee of: MacroGenics, R. Burns Employee of: MacroGenics, H. Li Employee of: MacroGenics, H. Li Employee of: MacroGenics, J. Muth Employee of: MacroGenics, R. Goldwater Employee of: Parexel, E. Bonvini Shareholder of: MacroGenics, Employee of: MacroGenics, S. Johnson Shareholder of: MacroGenics, Employee of: MacroGenics, P. Moore Shareholder of: MacroGenics, Employee of: MacroGenics, J. Wigginton Shareholder of: MacroGenics, Employee of: MacroGenics